2020
DOI: 10.3389/fonc.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife Stereotactic Body Radiation Therapy as an Effective Treatment for Hepatocellular Carcinoma Patients With Decompensated Cirrhosis

Abstract: The aim of our study was to evaluate the curative effect and safety of CyberKnife stereotactic body radiation therapy in treating decompensated cirrhosis hepatocellular carcinoma (HCC) patients. Methods: From March 2011 to December 2015, 32 HCC patients who refused or were ineligible for other treatments were treated with CyberKnife stereotactic body radiation therapy. Among these patients, 17 were Child-Pugh score 7 (53.13%), 7 were Child-Pugh score 8 (21.87%), 4 were Child-Pugh score 9 (12.50%), and 4 were C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our previous retrospective study [3] showed that for the HCC patients with decompensated cirrhosis, the overall survival rates of 1-year, 2-year and 3-year were 84.4%, 61.8% and 46.0%, respectively. The local control rates of 1 year, 2 years and 3 years were 92.9%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous retrospective study [3] showed that for the HCC patients with decompensated cirrhosis, the overall survival rates of 1-year, 2-year and 3-year were 84.4%, 61.8% and 46.0%, respectively. The local control rates of 1 year, 2 years and 3 years were 92.9%.…”
Section: Discussionmentioning
confidence: 97%
“…Stereotactic body radiation therapy (SBRT) has been an effective treatment for HCC patients, and our previous study [3] showed SBRT may provide new options for the treatment of decompensated cirrhosis patients. However, because the sample volume of our previous study was small and it was a retrospective study, the result may be biased.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the portal vein invasion are di cult to perform surgery, some other effective and safe options are needed. We have proven that Cyber-Knife SBRT (CK-SBRT) is safe for HCC patients with decompensated cirrhosis 4 , and we also found that the platelet count was an in uencing factor that affected the survival rates of patients with small HCC (including all patients who received CK-SBRT and hepatic resection) 5 . Therefore, we conducted this study to evaluate the e cacy and safety of stereotactic body radiation therapy (SBRT) in patients with the portal vein invasion (≤ 5 cm) and explore the association between pretreatment platelet count and out-eld recurrence and radiation-induced liver disease (RILD).…”
Section: Introductionmentioning
confidence: 91%
“…Combining TACE with systemic therapy has not so far shown significant improvement compared to TACE alone but further clinical trials are ongoing. Additional locoregional treatments include the stereotactic body radiotherapy "cyberknife" and targeted chemotherapy using Yttrium microspheres [112,113].…”
Section: Non-curative Treatmentsmentioning
confidence: 99%